Dinamika Penerapan Ijtihad Bidang Hukum Ekonomi Syariah Di Indonesia - Abdullah, Zaitun; Wijaya, Endra (UI Scholars Hub, 2019)
The development of Islamic economic conceptually and practically is so dynamic. In response to such condition, the presence of apt law becomes important to regulate or manage Islamic economic activities. Even though Al-Quran and Hadith already become main source and basic for all activities, but business actors still need several guidelines in doing Islamic economic activities. In this point, ijtihad could be such kind of instruments to help business actors run and involve in Islamic economic activities with its recent development. One of the forms of ijtihad is fatwa. In Indonesia, Indonesian Council of Ulama (Majelis Ulama Indonesia or MUI) is one of the formal institution who has authority to issue fatwa, and it also has special body, namely National Sharia Council (Dewan Syariah Nasional), to issue sharia economic activities fatwa. This paper will focus on several aspects of fatwa as form of ijtihad related to Islamic economic activities, including its dynamics and problems, such as binding capacity of the fatwa and readiness of the court to settle sharia business dispute